Study of clincial profile and outcome of Klebsiella sepsis in neonates at a tertiary care centre - N., Sharath Chandra; Sajjid, Mohamed; N., Kamalrathnam C.; V., Prakash (International Journal of Contemporary Pediatrics, 2019)
Background: Objective of the study is to study clinical profile and outcome of Klebsiella sepsis in neonates. Methods: A retrospective observational study from January 2018 to Sep 2018. After getting approval of institute ethics committee, admitted neonates whose blood culture showed Klebsiella growth were enrolled. A detailed history, birth weight, sex , age, APGAR, need for resuscitation at birth, distress at birth, ventilator support, CPAP, central line, blood products, species of Klebsiella and drug sensitivity and outcome-discharge or death were taken. Data were entered into Microsoft excel data sheet and was analyzed using SPSS 23 version software. Results: Out of the total 252 positive blood culture, 110 (43%) grew Klebsiella in blood culture. 92 cases were included in the study. Male to female ratio was 1.24:1. Mean age at admission was 1.22 days. 40 (43.5%) died and 52(56.5%) were discharged. Birth weight was 1.635±802 gm for babies who died and 2211±939 gm among discharged. Mean gestational age were 32.5 weeks in died and 34.8 weeks among discharged. Mortality was 23(57.5%) in males, low birth weight babies 23(59%), thrombocytopenia 28 (78%), invasive mode of ventilation 19(67%). By Univariate analysis, it was found that pregnancy induced hypertension (PIH), premature rupture of membrane (PROM), abnormal APGAR, Birth weight, shock, invasive ventilation, DIC, inotropes, blood products, abnormal total count, thrombocytopenia, umbilical venous catheterization were factors which influenced outcome. Regression analysis identified only thrombocytopenia and umbilical venous catheterization as factors that influenced outcome in Klebsiella sepsis. Klebsiella isolated was uniformly sensitive to Meropenam. Conclusions: No single risk factor was ascertained but thrombocytopenia and umbilical venous catheterization possibly influence the outcome of Klebsiella sepsis. Mortality is high in neonates.